EXPLAIN ME THIS: RESENHA SOBRE A OBRA DE ADELE GOLDBERG (2019) / Explain me this: review on Adele Goldberg’s book (2019) - Freitas Jr, Roberto; Alonso, Karen Sampaio Braga; de Oliveira, Manuela Correa (Pensares em Revista, 2020)
Resenha do livro Explain me This: Creativity, competition and partial productivity of constructions da Adele Goldberg